Professors' Expectations About Online Education and Its Relationship With Characteristics of University Entrance and Students' Academic Performance During the COVID-19 Pandemic - Lobos Peña, Karla; Bustos-Navarrete, Claudio; Cobo-Rendón, Rubia; Fernández Branada, Carolyn; Bruna Jofré, Carola; Maldonado Trapp, Alejandra (Frontiers in Psychology, 2021)
Background: Due to the COVID-19 universities have been challenged to generate the best possible experience for student with online academic training programs. Aim: to analyze professor’s expectations about online education, and relate them to student academic performance during the COVID-19 pandemic, considering the socio-demographic, entry, and prior university performance variables of students. Method: prospective longitudinal design, analyzing in T1 the expectations of 546 professors (54.8% male). In T2, the impact of the expectations of 382 of these professors (57.6% men) was analized, who took courses during the first semester to a total of 14838 university students (44.6% men). The professors’ expectations and their previous experience in online courses were obtained during T1, the students' academic information was obtained in T2. The questionnaire of Expectations towards Virtual Education in Higher Education for Professors was used. Results: 84.9% of the professors considered to have moderate to high skills for online courses. Differences in expectations were found according to the professors’ training level. The professors’ Self-efficacy dimensions for online education, Institutional Engagement, and Academic Planning were the highest scores. Professors expectations did not directly change the academic performance of their students; however, a moderating effect of professor’s expectations was identified in the previous student academic performance relationship on their current academic performance, the findings are discussed